Climate policy uncertainty and environmental degradation: Does democracy moderate this relationship? - Antonios Persakis; Ioannis Tsakalos; Vasileios Gkonis; Michail Nerantzidis (Cleaner Environmental Systems)
This study investigates the impact of climate policy uncertainty on environmental degradation and examines the moderating role of democracy in this relationship. Utilizing annual data from 126 economies spanning the years 1996–2021, and employing dynamic least squares and fully modified ordinary least squares models, the analysis reveals a significant negative relationship between climate policy uncertainty and environmental degradation. The findings indicate that higher uncertainty in climate policies is associated with reduced environmental degradation, suggesting that uncertainty in climate policies can drive cautious and ecologically conscious behaviors. Additionally, the study finds that democracy amplifies this negative relationship, implying that democratic environments enhance the effectiveness of climate policies in reducing environmental degradation which is attributed to greater transparency, accountability, public participation, and policy stability inherent in democratic systems. The study offers valuable practical implications for policymakers by highlighting how political and economic systems can influence environmental outcomes amid climate change.